2020
DOI: 10.1177/0081246320923819
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress in police detective officers dealing with complainants of sexual crimes

Abstract: The present study aimed to investigate the relationship between exposure to traumatised complainants and secondary traumatic stress. It also established the occurrence of secondary traumatic stress and the degree to which police detective officers reported secondary traumatic stress symptoms. Data were obtained on 51 police detective officers working in the Family Violence, Child Protection and Sexual Offences unit of the South African Police Service. A quantitative, correlational research design was employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…High intensities of STS symptoms have also been observed in the representatives of emergency services helping children who have suffered trauma, particularly policemen. The majority of police detectives from the South African Police Service who worked in the Family Violence, Sexual Offences and Child Protection unit (Cronje & Vilakazi, 2020) reported some degree of STS symptoms, which the authors attribute to frequent exposure to traumatised complainants. Research conducted in Wales and England among police officers from the Child Abuse Investigation Unit indicated that increased exposure to childhood sexual abuse was connected with a higher degree of STS (Hurrell et al, 2018).…”
Section: Sts Among Police Officersmentioning
confidence: 92%
“…High intensities of STS symptoms have also been observed in the representatives of emergency services helping children who have suffered trauma, particularly policemen. The majority of police detectives from the South African Police Service who worked in the Family Violence, Sexual Offences and Child Protection unit (Cronje & Vilakazi, 2020) reported some degree of STS symptoms, which the authors attribute to frequent exposure to traumatised complainants. Research conducted in Wales and England among police officers from the Child Abuse Investigation Unit indicated that increased exposure to childhood sexual abuse was connected with a higher degree of STS (Hurrell et al, 2018).…”
Section: Sts Among Police Officersmentioning
confidence: 92%
“…This sampling procedure is best described as purposive criterion sampling that is “reviewing and studying ‘all cases that meet some predetermined criterion of importance’” (Patton, 2002, p. 238, cited in Suri, 2011 ). This procedure is applied both in qualitative and quantitative studies ( Cronje and Vilakazi, 2020 ) . For reasons of confidentiality, an anonymous paper-and-pen survey, with stamped and addressed envelopes for return use, was distributed by postal mail primo 2020.…”
Section: Methodsmentioning
confidence: 99%
“…The study of compassion fatigue within police organizations is also a growing field, after critiques such as Andersen and Papazoglou’s (2015) on the existing gap in the research literature. Its research has also focused on particularly traumatic experiences and crimes, such as sexual and other extremely violent situations (Cronje & Vilakazi, 2020; Hurell et al, 2018). Police officers have also been found to experience low compassion satisfaction, with this dimension having a negative association with burnout and compassion fatigue (Grant et al, 2019).…”
Section: Police Resiliencementioning
confidence: 99%